2011
DOI: 10.1371/journal.ppat.1001278
|View full text |Cite
|
Sign up to set email alerts
|

NS2 Protein of Hepatitis C Virus Interacts with Structural and Non-Structural Proteins towards Virus Assembly

Abstract: Growing experimental evidence indicates that, in addition to the physical virion components, the non-structural proteins of hepatitis C virus (HCV) are intimately involved in orchestrating morphogenesis. Since it is dispensable for HCV RNA replication, the non-structural viral protein NS2 is suggested to play a central role in HCV particle assembly. However, despite genetic evidences, we have almost no understanding about NS2 protein-protein interactions and their role in the production of infectious particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
196
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(208 citation statements)
references
References 68 publications
(150 reference statements)
11
196
0
1
Order By: Relevance
“…NS2 and p7) (24 -26) do not localize to LDs in the absence of core or NS5A and do not interact with DGAT1 in our assays. These factors seem to be required at later stages in infectious particle production and regulate relocation of core from LDs to the ER as well as association of viral envelope protein E2 with viral factors, such as core and NS5A (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…NS2 and p7) (24 -26) do not localize to LDs in the absence of core or NS5A and do not interact with DGAT1 in our assays. These factors seem to be required at later stages in infectious particle production and regulate relocation of core from LDs to the ER as well as association of viral envelope protein E2 with viral factors, such as core and NS5A (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…One well-characterized ion channel-independent p7 function is its interaction with NS2, targeting the latter to defined loci within infected cells where it is thought to act as a 'particle assembly scaffold' (Boson et al, 2011;Jirasko et al, 2008Jirasko et al, , 2010Ma et al, 2011;Popescu et al, 2011;Stapleford & Lindenbach, 2011;Tedbury et al, 2011). p7 and NS2 in concert control sub/genotypedependent compartmentalization of HCV core protein between the ER and lipid droplets, with more efficient particle production resulting from ER-associated core (Boson et al, 2011).…”
Section: Hcv P7mentioning
confidence: 99%
“…Cell imaging shows that the RC lies proximal to sites where virus assembly probably occurs, since double-stranded RNA and MAF colocalize with envelope proteins and core-coated lipid droplets (30)(31)(32); the latter structures are thought to represent both a repository and a transitionary step in the maturation of core from a monomeric protein to a capsid shell (33,34). In addition, it has been conclusively demonstrated that mutations in the NS proteins can affect the efficiency of virus particle production independently of any effect that these changes may have on RNA replication (30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
mentioning
confidence: 99%